Galaxy Zoo: the fraction of merging galaxies in the SDSS and their morphologies - Darg, D; Kaviraj, S; Lintott, C; Schawinski, K; Sarzi, M; Bamford, S; Silk, J; Proctor, R; Andreescu, D; Murray, P; Nichol, R; Raddick, M; et al. (2009)
We present the largest, most homogeneous catalogue of merging galaxies in the nearby universe obtained through the Galaxy Zoo project - an interface on the world-wide web enabling large-scale morphological classification of galaxies through visual inspection of images from the Sloan Digital Sky Survey (SDSS). The method converts a set of visually-inspected classifications for each galaxy into a single parameter (the `weighted-merger-vote fraction,' $f_m$) which describes our confidence that the system is part of an ongoing merger. We describe how $f_m$ is used to create a catalogue of 3003 visually-selected pairs of merging galaxies from the SDSS in the redshift range $0.005 < z <0.1$. We use our merger sample and values of $f_m$ applied to the SDSS Main Galaxy Spectral sample (MGS) to estimate that the fraction of volume-limited ($M_r < -20.55$) major mergers ($1/3 < M^*_1/M^*_2 < 3$) in the nearby universe is $1 - 3 × C%$ where $C \sim 1.5$ is a correction factor for spectroscopic incompleteness. Having visually classified the morphologies of the constituent galaxies in our mergers, we find that the spiral-to-elliptical ratio of galaxies in mergers is higher by a factor $\sim 2$ relative to the global population. In a companion paper, we examine the internal properties of these merging galaxies and conclude that this high spiral-to-elliptical ratio in mergers is due to a longer time-scale over which mergers with spirals are detectable compared to mergers with ellipticals.